THE GROWTH DYNAMICS ON TREE SPECIES OF FAGACEAE FAMILY IN A TROPICAL MONTANE RAIN FOREST OF WEST JAVA, INDONESIA - Herwint Simbolon (BERITA BIOLOGI, 2001)
A one ha (100 x 100 m ) permanent plot each was established at sub-mountain (1000 m altitude) and mountain forests (1800 m altitude)in Gunung Halimun National Park,West Java in 1996.Both plots were monitored periodically in order to understand the population dynamics of tree species, an important aspect on understanding forest ecology.Number of individuals and total basal areas of Fagaceae species represented about 10 and 20.5% of total species in sub-mountain and 38 and 56.1% of total species in mountain forest.The distribution pattern of tree height(H, in m) of the similar diameter (D in cm) was consistently lower in mountain forest than of sub-mountain forest.The highest mortality index in sub-mountain and mountain forests was occurred on Lithocarpus sp.(ruui) and Castanopsis acuminatissima, respectively.As a whole, in both study sites, number of mortal individuals of all Fagaceae species during 1996-200 was higher than of recruit individuals.The growth and population dynamics of the Fagaceae species in both sites within 1996-2000 study periods were also discussed.